Characterization of wooden breast myopathy: a focus on syndecans and ECM remodeling - Pejšková, Lucie; Rønning, Sissel Beate; Kent, Matthew Peter; Solberg, Nina Therese; Høst, Vibeke; Thu-Hien, To; Wold, Jens Petter; Lunde, Marianne; Mosleth, Ellen; Pisconti, Addolorata; Kolset, Svein Olav; Carlson, Cathrine Rein; et al. (Frontiers in Physiology, 2023)
The skeletal muscle deformity of commercial chickens (Gallus gallus), known as the Wooden breast (WB), is associated with fibrotic myopathy of unknown etiology. For future breeding strategies and genetic improvements, it is essential to identify the molecular mechanisms underlying the phenotype. The pathophysiological hallmarks of WB include severe skeletal muscle fibrosis, inflammation, myofiber necrosis, and multifocal degeneration of muscle tissue. The transmembrane proteoglycans syndecans have a wide spectrum of biological functions and are master regulators of tissue homeostasis. They are upregulated and shed (cleaved) as a regulatory mechanism during tissue repair and regeneration. During the last decades, it has become clear that the syndecan family also has critical functions in skeletal muscle growth, however, their potential involvement in WB pathogenesis is unknown. In this study, we have categorized four groups of WB myopathy in broiler chickens and performed a comprehensive characterization of the molecular and histological profiles of two of them, with a special focus on the role of the syndecans and remodeling of the extracellular matrix (ECM). Our findings reveal differential expression and shedding of the four syndecan family members and increased matrix metalloproteinase activity. Additionally, we identified alterations in key signaling pathways such as MAPK, AKT, and Wnt. Our work provides novel insights into a deeper understanding of WB pathogenesis and suggests potential therapeutic targets for this condition.